Dampak kualitas tidur buruk bagi kesehatan tubuh - Afandi, Salsabila Tsuraya (Maliki Interdisciplinary Journal, 2024)
Sleep quality is when a person feels easy to fall asleep, can maintain sleep and feel relaxed after waking up. Sleep quality is said to be good if there are no signs of sleep deprivation such as impaired concentration, feeling unwell when awakened from sleep, and health problems. Poor sleep quality causes physiological and psychological health problems. The purpose of this study was to determine the impact that occurs on the health of the body if the quality of sleep is poor. In this study using qualitative methods, which were obtained from journals and the results of research that has been done by previous researchers. The objects used are newborns, children aged 3 to 5 years, adolescents, adults and the elderly. An analysis of several global population studies shows that children who sleep less than 10 hours a night are more likely to be obese than children who sleep more than 10 hours. Another study in adults also showed that people who slept less than 5 hours a night were more likely to be obese, according to a body mass index that increased for every hour they slept less